2011
DOI: 10.1590/s0103-05822011000400033
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome de Guillain-Barré em associação temporal com a vacina influenza A

Abstract: OBJETIVO: Descrever um caso de síndrome de Guillain-Barré em associação temporal com a vacina influenza A (H1N1) 2009. DESCRIÇAO DO CASO: Menino de quatro anos com queixa inicial de dor em coxa direita e perda de força muscular ascendente 15 dias após a segunda dose da vacina influenza A (H1N1) 2009. Ao exame neurológico apresentava tetraparesia e arreflexia, com predomínio em membros inferiores. A eletroneuromiografia evidenciou redução da velocidade e bloqueio de condução neuronal, com discreta perda axonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 17 publications
1
2
0
7
Order By: Relevance
“…Another study revealed that the highest incidence rate was shown by demyelinating forms (57%), followed by AMAN (24%) and AMSA (15%), in the Federal District 13 . A previous study 14 reported that men are more susceptible to GBS than women; this finding is in line with that of the current study (male-to-female ratio, 1.7:1).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Another study revealed that the highest incidence rate was shown by demyelinating forms (57%), followed by AMAN (24%) and AMSA (15%), in the Federal District 13 . A previous study 14 reported that men are more susceptible to GBS than women; this finding is in line with that of the current study (male-to-female ratio, 1.7:1).…”
Section: Discussionsupporting
confidence: 93%
“…Previously, a meta-analysis estimated the overall annual incidence rate of GBS to be 0.8-2 cases/100,000 individuals 14 . In Latin America, high incidence rates have been reported in Chile (2.12 cases/100,000) 15 and Argentina (2.06 cases/100,000) 16 , while a relatively low annual incidence rate has been reported in Brazil (0.4 cases/100,000) 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Essa síndrome é associada à vacina Influenza, desde o primeiro aparecimento em 1976. Cabe ressaltar, que o próprio Vírus da Influenza pode desencadear a SGB, mas não é muito frequente 18 .…”
Section: Resultsunclassified
“…Acredita-se que a doença seja desencadeada por uma resposta imune exacerbada a infecções recentes, resultando em um ataque imunológico direcionado aos nervos periféricos e suas raízes espinais (MALEK e SALAMEH, 2019). A desmielinização de nervos periféricos ocasiona fraqueza muscular de predomínio distal em diferentes graus, com caráter progressivo e ascendente, acompanhada por disfunções autonômicas e sensoriais, ocasionadas pela perda dos reflexos tendinosos profundos, que podem comprometer face, membros superiores e inferiores e também os músculos respiratórios (FERRARINI et al, 2011;CUNHA et al, 2019).…”
Section: Síndrome De Guillain-barréunclassified